The Aesthetic of Art Formation in the Decorations of Ibn Yusuf’s School Facades - Medjedoub, Sihem (Journal of Human Sciences, 2021)
Islamic architecture and its arts arose in the light of the teachings of Islam and developed through its various eras. In the Marinid era, the decorations of the Moroccan architecture showed many of the characteristics of the Islamic art through the ornamental cladding that embellishes its architectural facades, which vary between the facades of the courtyard (the place of ventilation) and the prayer hall (the mihrab). The facades of Ibn Youssef School in Marrakech were unique in forming aesthetic decorations for the various geometric, botanical and written decorative themes that adorned its surfaces. All this allow the viewer’s eye to perceive the facade with all the added decorative elements, thus reducing the material mass of the building, filling the spaces, and achieving equivalence between shapes and spaces on its surfaces.